Adaptive Constructivist Mobility Cycle (ACMC) sebagai Kerangka Konseptual Evaluatif Pendekatan Konstruktivisme Terhadap Program Indonesian International Student Mobility Awards (IISMA) sebagai Kebijakan Internasionalisasi Pendidikan di Indonesia - Muhammad Nurfajrin Nasri, A (Jurnal Manajemen dan Ilmu Administrasi Publik (JMIAP), 2025)
The Indonesian International Student Mobility Awards (IISMA) program, an initiative by Indonesia's Ministry of Education, Culture, Research, and Technology, aims to enhance students' academic and global competencies through international mobility. This study, the first to specifically connect the IISMA program with a constructivist approach within a policy framework, also proposes a conceptual framework: the Adaptive Constructivist Mobility Cycle (ACMC). A Systematic Literature Review (SLR) reveals that while IISMA positively impacts students' global perspectives, soft skills development, and cultural adaptation, significant challenges remain. These include academic credit transfer, post-program institutional support, and cultural and social barriers. Consequently, this study underscores the critical role of implementing constructivist principles in IISMA to ensure more meaningful and applicable learning experiences. Key policy recommendations include strengthening credit transfer mechanisms, enhancing academic and psychosocial support, and optimizing experience-based learning approaches in international mobility programs.